GCP compliance and readability of informed consent forms from an emerging hub for clinical trials - Nair, Satish Chandrasekhar (Perspect Clin Res, 2015)
BACKGROUND: The rapid expansion of trials in emerging regions has raised valid concerns about research subject protection, particularly related to informed consent. The purpose of this study is to assess informed consent form (ICF) compliance with Good Clinical Practice (GCP) guidelines and the readability easeof the ICFs in Abu Dhabi, a potential destination for clinical trials in the UAE. MATERIALS AND METHODS: A multicenter retrospective cross-sectional analysis of 140 ICFs from industry sponsored and non-sponsored studies was conducted by comparing against a local standard ICF. Flesch-Kincaid Reading Scale was used to assess the readability ease of the forms. RESULTS: Non-sponsored studies had significantly lower overall GCP compliance of 55.8% when compared to 79.5% for industry sponsored studies. Only 33% of sponsored and 16% of non-sponsored studies included basic information on the participants' rights and responsibilities. Flesch-Kincaid Reading ease score for the informed consent forms from industry sponsored studies was significantly higher 48.9 ± 4.8 as compared to 38.5 ± 8.0 for non-sponsored studies, though both were more complex than recommended. Reading Grade Level score was also higher than expected, but scores for the ICFs from the industry sponsored studies were 9.7 ± 0.7, significantly lower as compared to 12.2 ± 1.3 for non-sponsored studies. CONCLUSION: In spite of the undisputed benefits of conducting research in emerging markets readability, comprehension issues and the lack of basic essential information call for improvements in the ICFs to protect the rights of future research subjects enrolled in clinical trials in the UAE.